Time evolution of the structure function and dynamical scaling in porous SnO2 dry gels - Craievich, A. F.; Santilli, Celso Valentim [UNESP]; Pulcinelli, Sandra Helena [UNESP] (Elsevier, 1995)
An in situ study of the structural evolution of a porous SnO2 dry gel, under isothermal conditions, was carried out by means of the SAXS technique. The time evolution of the structure function is in agreement with the predictions of computer simulations for advanced stages of phase separation in binary materials. Dynamical scaling properties of the structure function of the porous system were verified. This study suggests that the evolution of microporosity occurs by a pure coagulation mechanism. © 1995.